2013
DOI: 10.3892/or.2013.2259
|View full text |Cite
|
Sign up to set email alerts
|

Expression of death receptor-3 in human breast cancer and its functional effects on breast cancer cells in vitro

Abstract: Death receptor-3 (DR3) plays controversial roles in cancer. Currently, DR3 is known to be a functional receptor of vascular endothelial growth inhibitor (VEGI). The role of DR3 in breast cancer remains unclear. The present study investigated DR3 expression in a clinical cohort of breast cancer patients and its role in breast cancer cells in vitro. The expression of DR3 was examined in a breast cancer cohort using quantitative PCR (Q-PCR) and immunohistochemistry (IHC) in comparison to the patients' data. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Notably, a similar association with adverse outcomes appears to take place in HCC also, as it was shown that higher local or systemic DcR3 expression in this population was associated with advanced TNM stage or increased incidence of local invasion or distant metastasis [14]. A similar positive correlation of elevated DcR3 expression with unfavorable disease course was also noted not only in other neoplasms [7, 8] but also in nonneoplastic conditions [1013]. Taken together, these results indicate that finding a highly elevated DcR3 concentration in patients with chronic inflammatory or neoplastic conditions, including chronic liver disease, may be considered a poor prognostic factor.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Notably, a similar association with adverse outcomes appears to take place in HCC also, as it was shown that higher local or systemic DcR3 expression in this population was associated with advanced TNM stage or increased incidence of local invasion or distant metastasis [14]. A similar positive correlation of elevated DcR3 expression with unfavorable disease course was also noted not only in other neoplasms [7, 8] but also in nonneoplastic conditions [1013]. Taken together, these results indicate that finding a highly elevated DcR3 concentration in patients with chronic inflammatory or neoplastic conditions, including chronic liver disease, may be considered a poor prognostic factor.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, DcR3 has also been shown to block proinflammatory signals mediated by the aforementioned TNF/TNFRSF ligand-receptor pairs. In line with these functional data, expression studies have clearly demonstrated overexpression of DcR3 in a variety of inflammatory and neoplastic conditions [58]. A distinctive property of DcR3 is that it lacks a transmembrane region and exists only as soluble protein, which can be accurately determined in biological fluids [9].…”
Section: Introductionmentioning
confidence: 96%
“…Beside autoimmune diseases, a role for the TL1A/DR3 system in atherosclerosis [133] and tumourigenesis [145,146] has been reported. In the chemoresistant human pancreatic cancer cell line AsPC-1, DR3-induced pro-inflammatory NFκB signalling correlated with enhanced cell proliferation and invasiveness, but the underlying molecular mechanism remained unclear [145].…”
Section: Structure Physiology and Pathophysiology Of Tnfr1 Trailmentioning
confidence: 99%
“…[7] It binds to Fas ligand (FasL) and inhibits FasL-induced apoptosis. Recent studies reported that expression of the DcR3 was minimal in normal tissues, but it was highly expressed in various types of tumors such as lung cancer,[78] esophageal cancer,[7] gastric cancer,[7] colon cancer,[7] colorectal cancer,[8] pancreatic cancer,[8] HCC,[8910] kidney cancer,[11] breast cancer,[812] ovarian cancer,[13] and skin cancer. [14] The gene was found amplified in about half of the primary lung and colon tumors studied.…”
Section: Introductionmentioning
confidence: 99%